The Prevalence and Outcomes of Transradial Percutaneous Coronary Intervention for ST-Segment Elevation Myocardial Infarction: Analysis From the National Cardiovascular Data Registry (2007 to 2011) - Baklanov, Dmitri V. (2012)
OBJECTIVES: The purpose of this study was to examine use and describe outcomes of radial access for percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI). BACKGROUND: Transradial PCI (TRI) is associated with reduced risk of bleeding and vascular complications, as compared with femoral access PCI (FPCI). Studies have suggested that TRI may reduce mortality among patients with STEMI. METHODS: We examined 294,769 patients undergoing PCI for STEMI at 1,204 hospitals in the CathPCI Registry between 2007 and 2011. Patients were grouped according to access site used for PCI. The temporal trend in the rate of radial versus femoral approach was determined. For minimization of confounding, an inverse probability weighting analysis incorporating propensity scores was used to compare procedural success, post-PCI bleeding, door-to-balloon times, and in-hospital mortality between radial and femoral access. RESULTS: Over the 5-year period, the use of TRI versus FPCI in STEMI increased from 0.9% to 6.4% (p < 0.0001). There was no difference in procedural success. TRI was associated with longer median door-to-balloon time (78 vs. 74 min; p < 0.0001) but lower adjusted risk of bleeding (odds ratio [OR]: 0.62; 95% CI: 0.53 to 0.72; p < 0.0001) and lower adjusted risk of in-hospital mortality (OR: 0.76; 95% CI: 0.57 to 0.99; p = 0.0455). CONCLUSIONS: In this large national database, use of radial access for PCI in STEMI increased over the study period. Despite longer door-to-balloon times, the radial approach was associated with lower bleeding rate and reduced in-hospital mortality. These data provide support to execute an adequately powered randomized controlled trial comparing radial and femoral approaches for PCI in STEMI.